KARAKTERISTIK DAN DUKUNGAN TENAGA KESEHATAN TERHADAP PRAKTIK GENITAL HYGIENE IBU HAMIL DI KOTA SEMARANG 2015 - Rizky Amelia; Zahroh Shaluhiyah; Cahya Tri Utami (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2015)
Cases of bacterial vaginosis in pregnant women in the city of Semarang based on data from Semarang City Hospital has increased over the last 3 years, in 2011 (4.8%), 2012 (5.4%), and 2013 (5.8%). Bacterial vaginosis in pregnancy can cause preterm labor, KPD, intra-uterine infection and infection pascasectio. The study aimed to describe and analyze the characteristics of respondents and support health workers may be related to the practice of maintaining the cleanliness of the genitalia (genital hygiene) in pregnant women in the city of Semarang. This type of research is explanatory research with cross sectional approach. Subject of the study 379 pregnant women his data taken from 16 health centers in the city of Semarang. Data were collected through questionnaires. Analysis of the data in this research is the data analysis of univariate, bivariate data analysis with chi square test. The majority of survey respondents aged ≥ 50% 28 years, multigravida, ANC regularly, never have complaints on the genitalia, education past high school, do not work with most trimester gestational age 3. Practice good genital hygiene category (60.1%) , variables related to the practice of genital hygiene education scheme (p value 0.0045) and support health workers (p value 0.026) with α 0,05. Puskesmas as the nearest health facility with the community will need to provide information genital hygiene practices through health promotion activities through Posyandu activities, ANC, class of pregnant women and health promotion activities that have been routinely implemented.